OP39 Psychological distress in the first year of fatherhood: the influence of preterm birth on father's later wellbeing. (2nd September 2014) - Carson, C; Redshaw, M; Gray, R; Quigley, MA
Abstract : Background: The early days of fatherhood are a time of great change, bringing both joy and stress. This period is associated with an increased risk of depression and anxiety in men, but the impact of perinatal factors, such as preterm birth, emergency delivery or a sick baby, on fathers' mental health has not been adequately assessed. Psychological distress (PD) in new fathers may not only adversely affect the individual, but also the family and the future wellbeing of the child. Methods: We explored the association between preterm birth and fathers' psychological well-being using data from the UK Millennium Cohort Study. First time fathers, who responded to the baseline questionnaire in 2000–2001 when their child was 9 months of age, are included. They completed the Rutter Malaise Inventory, a validated, self-reported measure of PD; a threshold of >4 identified those exhibiting signs of distress. Gestational age was reported by the mother, validated against hospital records, and grouped as very preterm (<32 weeks), moderately preterm (32–33 weeks), late preterm (34–36 weeks) and term ( >37 weeks). Data on potential confounding factors were also available, including father's socio-demographic and economic circumstances, father's own health, partner's wellbeing and relationship quality. Multivariable logistic regression was used to estimate odds ratios in Stata 13, using weights to account for design and response effects. Results: 10, 769 fathers are included in the analysis, of whom 953 (8.6%) exhibited signs of PD 9 months after the birth of their child. In unadjusted analysis, fathers of very and moderately preterm babies were twice as likely to report PD as those whose babies were born at term (<32 weeks: OR 2.0, 95% CI 1.1–3.7; 32–33 weeks, OR 2.0, 95% CI 1.1–3.5; 34–36 weeks, OR 1.2, 95% CI 0.8–1.6). After adjusting for confounding of socio-demographic and economic circumstances, mother's PD and fathers past history of depression, a significantly increased risk of PD remained in the moderately preterm (32–33 weeks, OR 2.1, 95% CI 1.1–3.9) but the effect was reduced in the smaller group of fathers of very preterm babies (<32 weeks, OR 1.3, 95% CI 0.8–2.4). Conclusion: Nearly 1 in 10 new fathers exhibited signs of psychological distress, and the risk of PD was higher among those men whose babies were born moderately or very preterm than at term. Health care professionals should pay close attention to the wellbeing of fathers of preterm babies, with support provided for the individual or family, if required.